UPAYA MENINGKATKAN PEMAHAMAN SISWA KELAS MELALUI METODE COORPERATIVE INTEGRATED READING AND COMPOSITION - Gumelar, Yusup (MGMP PAI Jawa Barat, 2023)
This research aims to improve the learning outcomes of class VIII D students at SMP Negeri 4 Purwadadi, regarding halal food and drinks and avoiding haram ones through the cooperative integrated reading and composition (CIRC) method. The research participants were 34 students in class VIII D of SMP Negeri 4 Purwadadi. The results of the research showed an increase in student learning outcomes collected in cycle I and cycle II in class VIII D student learning outcomes. The percentage increase in understanding in cycle I was from 38.23% to 91.17% in cycle II. Based on the research results, it can be concluded that the cooperative integrated reading and composition (CIRC) learning method is effective in improving the learning outcomes of class VIII D students at SMP Negeri 4 Purwadadi on halal food and drink material and avoiding haram ones. Keywords : Food and drink, learning outcomes, CIRC Method